A Review on the Therapeutic Potential of Herbal Remedies for Asthma - Porwal, Mayur; Rastogi, Vaibhav; Saxena, Divyam; Kumar, Anil (Current Traditional Medicine, 2026)
In modern society, asthma has emerged as a highly prevalent and chronic health concern, with its incidence and severity on the rise. This review's primary objective is to systematically assess the therapeutic potential of herbal interventions in the management of asthma. Herbal treatments have displayed noteworthy efficacy in alleviating asthmatic symptoms and improving control in a substantial subset of the afflicted population. While a multitude of pharmaceutical agents for asthma management exist, their ability to deliver sustained symptom relief is often limited, and concerns about unintended side effects have garnered considerable attention. Notable improvements in patient outcomes have been observed when traditional asthma therapies are complemented with herbal remedies. Given the widespread use of herbal supplements, there is an urgent need for well-designed randomized clinical trials to establish the efficacy and safety of herbal medicines for asthma. Although anecdotal reports suggest relief from asthma symptoms through herbal supplementation, a judicious and evidence-based approach is essential, weighing a herb's efficacy against the quality of supporting studies and its established safety profile. Simultaneously, our investigation encompassed an extensive dataset comprising 101 plants, each characterized by diverse phytochemical categories and their respective quantifications. Alkaloids emerged as notably abundant, signifying their ubiquity, while several categories, such as fatty acids, iridoids, phenylethanoids, polyphenols, polysaccharides, sesquiterpene lactones, steroids, styryl lactones, sulfur-containing compounds, and xanthones were relatively rare. Notably, the diversity within phenolic compounds, especially the prevalence of flavonoids, underscores their significance in botanical chemistry. Triterpenoids were identified as vital components within this dataset. This dataset not only enriches our understanding of phytochemical diversity but also provides a foundational resource for further scientific exploration. It equips researchers from diverse disciplines with essential insights that may catalyze the development of innovative therapies and pharmaceuticals. Therefore, this dual approach, investigating herbal interventions in asthma management and elucidating phytochemical richness, substantially advances our scientific knowledge and holds promise for improving the quality of life for individuals living with asthma.
Keywords: herbs